2014
DOI: 10.1088/0967-3334/35/2/189
|View full text |Cite
|
Sign up to set email alerts
|

Measuring skin temperature before, during and after exercise: a comparison of thermocouples and infrared thermography

Abstract: Measuring skin temperature (T SK ) provides important information about the complex thermal control system and could be interesting when carrying out studies about thermoregulation. The most common method to record T SK involves thermocouples at specific locations; however, the use of infrared thermal imaging (IRT) has increased. The two methods use different physical processes to measure T SK , and each has advantages and disadvantages. Therefore, the objective of this study was to compare the mean skin tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 50 publications
5
53
2
2
Order By: Relevance
“…This response occurred similarly in both groups. Others authors (Fernandes et al, 2014;Formenti et al, 2013) studied the thermal response during aerobic exercises and reported that ROIs which were not directly involved in exercise present a decrease in skin temperature. It occurred due to a cutaneous vasoconstriction reflex that redirecting blood flow to the active muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This response occurred similarly in both groups. Others authors (Fernandes et al, 2014;Formenti et al, 2013) studied the thermal response during aerobic exercises and reported that ROIs which were not directly involved in exercise present a decrease in skin temperature. It occurred due to a cutaneous vasoconstriction reflex that redirecting blood flow to the active muscles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences observed in T SKIN from TC were sizeable. Utilising TC in a dynamic, ecologically valid situation is in contrast to the techniques adopted in the majority of previous research with thermal cameras that has shown broadly encouraging results (Merla et al 2010;Ferreira et al 2008;Chudecka & Lubkowska 2012), albeit not unanimously (Fernandes et al 2014). Specifically, tripod mounted cameras have been used to generate thermograms of participants who have spent up to 40 minutes in thermo-neutral conditions.…”
Section: Skin Temperature Validity Comparisonmentioning
confidence: 99%
“…These factors include structural abnormalities of vessels (dilation and incompetence), abnormalities of vascular control, local effects on vessels, changes in thermal conductivity of the tissues, and increased heat production of the tissues, e.g., in inflammatory processes. Technological advances have made MIT a reliable medical measurement tool [25-29] for detecting both changes of skin temperature [32, 36] and their magnitude in inflammatory skin diseases [33, 37-40]. Moreover, it can be employed to objectively detect the therapeutic success of anti-inflammatory treatment [39, 40].…”
Section: Discussionmentioning
confidence: 99%